Language Training and Refugees’ Integration - Foged, Mette; Hasager, Linea; Peri, Giovanni; Arendt, Jacob Nielsen; Bolvig, Iben (The Review of Economics and Statistics, 2024)
Abstract We evaluate a Danish reform focused on improving language training for those granted refugee status on or after January 1, 1999. Using a Regression Discontinuity Design, we find a significant, permanent, positive effect on earnings. This effect emerged after completion of language classes and was accompanied by additional schooling and a higher probability of working in complex jobs, consistent with language training, rather than other minor aspects of the reform, producing the results.